Fabrication of Fully‐Spray‐Processed Organic Photovoltaic Modules by using an Automated Process in Air. Issue 12 (December 2013) - La Notte, Luca; Mineo, Daniel; Polino, Giuseppina; Susanna, Gianpaolo; Brunetti, Francesca; Brown, Thomas M.; Di Carlo, Aldo; Reale, Andrea
Abstract In organic photovoltaics, large‐area‐compatible and solution‐based processes are the best candidates for achieving high throughput at low cost. Among these, spray coating is a well‐established technique in the industry that can be successfully applied to polymer solar cells (PSCs). In this study we report the demonstration of an automated spray process, completely performed in air, to fabricate the first fully spray‐coated modules on glass/transparent‐conducting‐oxide (TCO) substrates. For this purpose we started with optical and electrical characterization of single layers (TiO2, P3HT:PCBM, PEDOT‐CPP, and PEDOT‐PH1000), to obtain films with the desired properties. Then, photovoltaic cells and modules were fabricated by increasing the number of sprayed layers (1‐layer, 2‐layers, and fully sprayed devices completely free from evaporation processes). Good reproducibility and encouraging electrical performances were obtained. In particular, the 1‐layer, 2‐layer, and full modules (active area=6 cm2) exhibited conversion efficiencies of 1.8 %, 1.3 %, and 0.9 %, respectively. Therefore, the feasibility of a scalable and reliable process for spraying all layers of a semitransparent PSC module were demonstrated here with the potential of being applicable to plastic substrates by the introduction of a low‐temperature‐processed layer in place of TiO2.